2017
DOI: 10.1200/jco.2017.35.15_suppl.tps11081
|View full text |Cite
|
Sign up to set email alerts
|

Tappas: An adaptive enrichment phase 3 trial of TRC105 and pazopanib versus pazopanib alone in patients with advanced angiosarcoma (AAS).

Abstract: TPS11081 Background: AAS is an aggressive soft tissue sarcoma (STS) of endothelial cell origin with an expected median overall survival of 8-12 months. Pazopanib (P) is approved for treatment of advanced STS following progression on chemotherapy. In a retrospective study of 40 AAS patients treated with single agent P the median PFS was 3.1 months and median OS 9.9 months with no complete responses. Endoglin is an essential angiogenic receptor expressed on AAS that is upregulated following VEGF inhibition, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The initial enrollment is 124 patients, but may expand up to a maximum of 200 patients. 78 The estimated primary completion date of the study is September 2018.…”
Section: Antibodies To Watch In 2018: Late-stage Antibody Therapeuticmentioning
confidence: 99%
“…The initial enrollment is 124 patients, but may expand up to a maximum of 200 patients. 78 The estimated primary completion date of the study is September 2018.…”
Section: Antibodies To Watch In 2018: Late-stage Antibody Therapeuticmentioning
confidence: 99%
“…Data from an earlier trial provided suggestive evidence that the treatment may have a greater likelihood of benefiting the subpopulation who enter the trial with cutaneous lesions compared with those with non‐cutaneous lesions. The TAPPAS trial design goals included having 80% power to detect a benefit (hazard ratio of 0.55 for progression‐free survival) in the combined population, and also 80% power to detect such a benefit only in the subpopulation with cutaneous lesions (Jones et al ., ). A two‐stage, adaptive enrichment design was implemented.…”
Section: Introductionmentioning
confidence: 89%
“…As an example, consider the phase 3 randomized trial of a treatment for angiosarcoma called the ‘TRC105 and pazopanib versus pazopanib alone in patients with advanced angiosarcoma trial’ (which is known as the ‘TAPPAS’ trial) (Jones et al ., ; Mehta et al ., ). Data from an earlier trial provided suggestive evidence that the treatment may have a greater likelihood of benefiting the subpopulation who enter the trial with cutaneous lesions compared with those with non‐cutaneous lesions.…”
Section: Introductionmentioning
confidence: 97%
“…Example TAPPAS [164,165] is a trial of TRC105 (an antibody) and pazopanib versus pazopanib alone in patients with advanced angiosarcoma. The study identified two sub-groups, those with cutaneous advanced angiosarcoma and those with non-cutaneous advanced angiosarcoma.…”
Section: Population Enrichmentmentioning
confidence: 99%